Comparative morphology and taxonomy of the tiger moth genus Epanycles Butler (Lepidoptera, Erebidae, Arctiinae, Arctiini, Ctenuchina), with notes on related genera - Araujo, Elias C.; Pinheiro, Lívia R.; Duarte, Marcelo (Zootaxa, 2019)
We studied the Neotropical genera Epanycles Butler, Sciopsyche Butler and Episcepsis Butler. We investigated the delimitation of Epanycles, which at the beginning of this work was monotypic, but had a history of other species placed in it, all of which are currently placed in genera to which they do not belong. Indeed, we found Epanycles to include only its type species, Euchromia imperialis Walker, here redescribed based on external and genitalic characters of both sexes from specimens covering most of its known geographical distribution. Our investigation included detailed studies of the species previously placed in Epanycles (Hyaleucerea gigantea (Druce) and Eucereon obscurum (Möschler)), and of species belonging to genera putatively closely related to it: Sciopsyche tropica (Walker), Episcepsis venata Butler, Episcepsis endodasia Hampson and Episcepsis luctuosa (Möschler). The characters separating all these taxa from Epanycles are discussed, and a mistake in the publication of Episcepsis atlantica Pinheiro & Araujo Jr. is corrected. The habitus and genitalia of the species herein treated are illustrated.